The Impact of “Fear of Falling” on Physical Performance, Balance, and Ambulation in Duchenne Muscular Dystrophy - Alemdaroğlu-Gürbüz, İpek; İpek, Canan; Bulut, Numan; Karaduman, Ayşe; Yılmaz, Öznur (Neuropediatrics, 2022)
Objective The aim of this study was to investigate falls and the fear of falling (FOF) in children with Duchenne muscular dystrophy (DMD) and to determine the relationships between the FOF and physical performance, balance, and ambulation.Methods Thirty-eight ambulatory children with DMD were included in the study. The functional level, falling history, FOF, physical performance, balance, and ambulation were assessed by using Brooke Lower Extremity Functional Classification, History of Falls Questionnaire, Pediatric Fear of Falling Questionnaire (Ped-FOF), timed performance tests, Timed “Up and Go” (TUG) test, and North Star Ambulatory Assessment (NSAA), respectively.Results Of the 38 children (mean age: 9.00 ± 2.03 years) 97.4% had a history of serious fall last year and 62.2% were injured due to this fall. The Ped-FOF score was 13.79 ± 7.20. Weak to moderate relations were determined between Ped-FOF and functional level (r = 0.33), frequency of falls (r = 0.41), duration of climbing 4-steps (r = 0.38), TUG (r = 0.36), and NSAA (r = –0.32) (p < 0.05).Conclusion Ambulatory children with better performance scores had lower levels of FOF despite their history of serious falls and injuries. FOF tends to increase as the symptoms of the disease progresses. Investigating the history of falls and FOF from the earliest period will guide to take precautions and make necessary interventions on time in treatment programs.
Keywords: Duchenne muscular dystrophy; fall history; fear of falling; balance ability; ambulation; physical performance